Identifikasi Stakeholder Pengelolaan Pemanfaatan Jasa Ekosistem di Taman Nasional Baluran - Joko Mulyo Ichtiarso (Wanamukti: Jurnal Penelitian Kehutanan, 2018)
Baluran National Park has an ecosystem service that’s used directly by the people of buffer village. The amount of benefits from these ecosystem services has not received attention in management activities in Baluran National Park. The last 5 years data on the number of tourist visits reached 176,888 tourists, namely 172,039 domestic tourists and 4,849 foreign tourists. However, villagers only play a role in providing tourist motorcycle taxi services. So that people have access to the use of ecosystem services. The purpose of this research is to identify of stakeholders of utilization ecosystem services management in Baluran National Park. The method of research uses quantitative and qualitative approaches, purposive sampling, and interviews using questionnaires. The Analyze is qualitative descriptions and analysis of policy contents. The result of this study is describe of stakeholders of utilization ecosystem service management in Baluran National Park accommodates various interests of stakeholders who can be involved in the management of the use of Baluran National Park ecosystem services.  Keywords: Management, Utilization Ecosystem Services, Baluran National Park